Urolithin A and B Alter Cellular Metabolism and Induce Metabolites Associated with Apoptosis in Leukemic Cells - Alzahrani, Abdulaziz Musa (Int J Mol Sci, 2021)
Leukemia is persistently a significant cause of illness and mortality worldwide. Urolithins, metabolites of ellagic acid and ellagitannins produced by gut microbiota, showed better bioactive compounds liable for the health benefits exerted by ellagic acid and ellagitannins containing pomegranate and walnuts. Here, we assessed the potential antileukemic activities of both urolithin A and urolithin B. Results showed that both urolithin A and B significantly inhibited the proliferation of leukemic cell lines Jurkat and K562, among which urolithin A showed the more prominent antiproliferative capability. Further, urolithin treatment alters leukemic cell metabolism, as evidenced by increased metabolic rate and notable changes in glutamine metabolism, one-carbon metabolism, and lipid metabolism. Next, we evidenced that both urolithins equally promoted apoptosis in leukemic cell lines. Based on these observations, we concluded that both urolithin A and B alter leukemic cell metabolome, resulting in a halt of proliferation, followed by apoptosis. The data can be used for designing new combinational therapies to eradicate leukemic cells.